Nanobowl Array Fabrication via Conglutination Process Based on Thiol–Ene Polymer - Man Zhang; Liangping Xia; Qiling Deng; Lifang Shi; Axiu Cao; Hui Pang; Song Hu (IEEE Photonics Journal, 2015)
The technique to fabricate nanostructures with high resolution is of crucial importance to nanosciences and nanotechnology. This paper presented a nonconventional method to fabricate metallic nanobowl arrays via the conglutination process, which relied on the high adhesive material to “stick” nanostructures. The ultraviolet (UV)-curable thiol-ene had low viscosity and was cured under UV light to form a cross-linked polymer with high Young's modulus and high surface energy via “click chemistry,” which was used as the adhesive material to firmly stick nanostructures from the mold. By using the method, a self-assembly polystyrene (PS) sphere template with a metallic layer was stuck by the cross-linked thiol-ene polymer from the substrate. After removing the PS spheres, the metallic nanobowl structure with the thiol-ene substrate was achieved. In this paper, we fabricated gold nanobowl arrays composed of nanoheaves with the average diameter of ca. 60 nm between nanobowls, which verified the feasibility of the fabrication method.